2014
DOI: 10.4028/www.scientific.net/amm.548-549.1601
|View full text |Cite
|
Sign up to set email alerts
|

Design Guidelines for Buildings in Saudi Arabia Considering Energy Conservation Requirements

Abstract: In Kingdom of Saudi Arabia (KSA), the contribution from buildings towards energy consumption, both residential and commercial, has steadily increased reaching figures of 35% to 40% in the past few years. For this reason, energy efficiency in buildings is a prime objective for energy policy at regional, national and international levels. This research aims to provide design guidelines for buildings in Saudi Arabia taking into consideration the energy conservation principles. The proposed design parameters/guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…On the other hand, it is well established from experimental study in [9], that the compressor ON/OFF cycle causes significant amount of efficiency and capacity loss. In addition, it is experimentally found that efficiency loss of the system is 9% and the capacity loss is 11% due to compressor motor ON/OFF cycling.…”
Section: Power Consumption Of On/off Hvac Unitmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it is well established from experimental study in [9], that the compressor ON/OFF cycle causes significant amount of efficiency and capacity loss. In addition, it is experimentally found that efficiency loss of the system is 9% and the capacity loss is 11% due to compressor motor ON/OFF cycling.…”
Section: Power Consumption Of On/off Hvac Unitmentioning
confidence: 99%
“…The energy demand in correspondence has grown at a much higher pace of approximately 5-8% per year [8]. Moreover, A/C systems are considered to be the major energy consumptions in the residential area in KSA and it is accounted for approximately 60% [9][10]. The significant focus in evaluating the performance of HVAC systems is ensuring the thermal comfort and reducing the energy consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, many residential areas around the world are characterized by hot and humid atmosphere, such as in the Arabian Gulf, Africa, S America, S. Asia, and part of USA. For example, the primary energy consumption in Saudi Arabia is the HVAC system which accounts for about 60% of the energy used in the houses [7]. Space-conditioning has gone on the rise throughout the Kingdom of Saudi Arabia (KSA) and also consumption of more energy has increased due to the severe hot temperature, high humidity, and dust storms.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Fabric first thermal retrofitting strategies have been reported to have the potential to reduce cooling loads by between 20 and 35%. [9][10][11] Cooling techniques such as ground pipe supply ventilation, evaporative and night radiative cooling, have been evaluated by two studies in climatic zones where temperatures are moderate. 12,13 The climate of KSAwhere peak summer temperatures can reach 50 C with high RH which presents a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%